Proofs aren't always easy to write out but I'll attempt a lengthier proof that I've recently seen. The assertion is that the proposition [p
→ (q → r)] → [(p → q) → (p → r)] is a tautology. We can approach this in a couple of different ways. One way would be to create a truth table, which I'll demonstrate below and the other will be to do it with inference laws. I'm not going to list out all of the inference laws, but will instead just work out the example.
The truth table should display True for all of the different combinations and as can be seen below it does.
Now for the fun part; to prove it using inference laws. To briefly describe what I'm doing, there are 2 parts to this proposition. The left part is: [p → (q → r)] and the right part is: [(p → q) → (p → r)]
I'll work on the left part first and then the right part.
[p → (q → r)] → [(p → q) → (p → r)]
[p → (¬q ∨ r)] → [(p → q) → (p → r)]
[¬p ∨ (¬q ∨ r)] → [(p → q) → (p → r)]
[¬p ∨ (¬q ∨ r)] → [(¬p ∨ q) → (¬p ∨ r)]
[¬p ∨ (¬q ∨ r)] → [¬(¬p ∨ q) ∨ (¬p ∨ r)]
[¬p ∨ (¬q ∨ r)] → [(p ∧ ¬q) ∨ (¬p ∨ r)]
[¬p ∨ (¬q ∨ r)] → [((p ∧ ¬q) ∨ ¬p) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [((¬p ∨ p) ∧ (¬p ∨ ¬q)) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [(T ∧ (¬p ∨ ¬q)) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [(¬p ∨ ¬q) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [¬p ∨ (¬q ∨ r)]
At this point we see that the left is identical to the right. If we let w = ¬p ∨ (¬q ∨ r), then w → w is True no matter what the Truth value of w is. If w is True then T → T is True; also, if w if False then F → F is also True. But just for the fun of it, lets see if we can get a nice T at the end.
¬[¬p ∨ (¬q ∨ r)] ∨ [¬p ∨ (¬q ∨ r)]
[p ∧ ¬(¬q ∨ r)] ∨ [¬p ∨ (¬q ∨ r)]
[p ∧ (q ∧ ¬r)] ∨ [¬p ∨ (¬q ∨ r)]
[p ∧ (q ∧ ¬r)] ∨ ¬p] ∨ [(¬q ∨ r)]
[(¬p ∨ p) ∧ (¬p ∨ q) ∧ (¬p ∨ ¬r)]] ∨ [(¬q ∨ r)]
[T ∧ (¬p ∨ q) ∧ (¬p ∨ ¬r)]] ∨ [(¬q ∨ r)]
[(¬p ∨ q) ∧ (¬p ∨ ¬r)]] ∨ [(¬q ∨ r)]
[(¬p ∨ q) ∧ (¬p ∨ ¬r)] ∨ ¬q] ∨ r
[(¬q ∨ (¬p ∨ q)) ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
[((¬q ∨ ¬p) ∨ (¬q ∨ q)) ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
[((¬q ∨ ¬p) ∨ T) ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
[T ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
(¬q ∨ (¬p ∨ ¬r)) ∨ r
((¬q ∨ ¬p) ∨ (¬q ∨ ¬r)) ∨ r
(r ∨ (¬q ∨ ¬p)) ∨ (r ∨ (¬q ∨ ¬r))
(r ∨ (¬q ∨ ¬p)) ∨ (¬q ∨ (r ∨ ¬r))
(r ∨ (¬q ∨ ¬p)) ∨ (¬q ∨ T)
[r ∨ (¬q ∨ ¬p)] ∨ T
T
The truth table should display True for all of the different combinations and as can be seen below it does.
p
|
q
|
r
|
q → r
|
p → (q → r)
|
p → q
|
p → r
|
(p → q) → (p → r)
|
[p → (q → r)] →
[(p → q) → (p → r)] |
T
|
T
|
T
|
T
|
T
|
T
|
T
|
T
|
T
|
T
|
T
|
F
|
F
|
F
|
T
|
F
|
F
|
T
|
T
|
F
|
T
|
T
|
T
|
F
|
T
|
T
|
T
|
T
|
F
|
F
|
T
|
T
|
F
|
F
|
T
|
T
|
F
|
T
|
T
|
T
|
T
|
T
|
T
|
T
|
T
|
F
|
T
|
F
|
F
|
T
|
T
|
T
|
T
|
T
|
F
|
F
|
T
|
T
|
T
|
T
|
T
|
T
|
T
|
F
|
F
|
F
|
T
|
T
|
T
|
T
|
T
|
T
|
Now for the fun part; to prove it using inference laws. To briefly describe what I'm doing, there are 2 parts to this proposition. The left part is: [p → (q → r)] and the right part is: [(p → q) → (p → r)]
I'll work on the left part first and then the right part.
[p → (q → r)] → [(p → q) → (p → r)]
[p → (¬q ∨ r)] → [(p → q) → (p → r)]
[¬p ∨ (¬q ∨ r)] → [(p → q) → (p → r)]
[¬p ∨ (¬q ∨ r)] → [(¬p ∨ q) → (¬p ∨ r)]
[¬p ∨ (¬q ∨ r)] → [¬(¬p ∨ q) ∨ (¬p ∨ r)]
[¬p ∨ (¬q ∨ r)] → [(p ∧ ¬q) ∨ (¬p ∨ r)]
[¬p ∨ (¬q ∨ r)] → [((p ∧ ¬q) ∨ ¬p) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [((¬p ∨ p) ∧ (¬p ∨ ¬q)) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [(T ∧ (¬p ∨ ¬q)) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [(¬p ∨ ¬q) ∨ r)]
[¬p ∨ (¬q ∨ r)] → [¬p ∨ (¬q ∨ r)]
At this point we see that the left is identical to the right. If we let w = ¬p ∨ (¬q ∨ r), then w → w is True no matter what the Truth value of w is. If w is True then T → T is True; also, if w if False then F → F is also True. But just for the fun of it, lets see if we can get a nice T at the end.
¬[¬p ∨ (¬q ∨ r)] ∨ [¬p ∨ (¬q ∨ r)]
[p ∧ ¬(¬q ∨ r)] ∨ [¬p ∨ (¬q ∨ r)]
[p ∧ (q ∧ ¬r)] ∨ [¬p ∨ (¬q ∨ r)]
[p ∧ (q ∧ ¬r)] ∨ ¬p] ∨ [(¬q ∨ r)]
[(¬p ∨ p) ∧ (¬p ∨ q) ∧ (¬p ∨ ¬r)]] ∨ [(¬q ∨ r)]
[T ∧ (¬p ∨ q) ∧ (¬p ∨ ¬r)]] ∨ [(¬q ∨ r)]
[(¬p ∨ q) ∧ (¬p ∨ ¬r)]] ∨ [(¬q ∨ r)]
[(¬p ∨ q) ∧ (¬p ∨ ¬r)] ∨ ¬q] ∨ r
[(¬q ∨ (¬p ∨ q)) ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
[((¬q ∨ ¬p) ∨ (¬q ∨ q)) ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
[((¬q ∨ ¬p) ∨ T) ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
[T ∧ (¬q ∨ (¬p ∨ ¬r))] ∨ r
(¬q ∨ (¬p ∨ ¬r)) ∨ r
((¬q ∨ ¬p) ∨ (¬q ∨ ¬r)) ∨ r
(r ∨ (¬q ∨ ¬p)) ∨ (r ∨ (¬q ∨ ¬r))
(r ∨ (¬q ∨ ¬p)) ∨ (¬q ∨ (r ∨ ¬r))
(r ∨ (¬q ∨ ¬p)) ∨ (¬q ∨ T)
[r ∨ (¬q ∨ ¬p)] ∨ T
T
Comments
Post a Comment